A rare case of primary peripheral epithelial myoepithelial carcinoma of lung: Case report and literature review. Issue 35 (August 2016) - Shen, Cheng; Wang, Xin; Che, Guowei
Abstract: Background: Primary salivary gland–type tumors of lung are rare. Epithelial–myoepithelial carcinoma (EMC) of the lung is a minor salivary gland–type tumor subtype. Methods: We report a very rare case of EMC located in the peripheral left lower lobe that was diagnosed in a 58-year-old man and this is the first study in which we summarize all the patients with primary peripheral lung EMC concerned with the clinical features. Informed consent was obtained from the patient. Results: Chest computed tomography displayed an anomalous soft tissue mass with slightly lobular borders in the peripheral segment of the left lower lobe and closed to the visceral pleura. The surgery was performed by using video-assisted thoracic surgery. Grossly, the tumor was solitary, well-circumscribed, and unencapsulated endobronchial lesion. A microscopic examination revealed that it was circumscribed, although the tumor borders may show single cells or clusters of cells proliferating away from the main tumor mass. The inner tubular layer showed epithelial cell characteristics, whereas the outer layer exhibited myoepithelial cell characteristics. Immunostaining for P40, P63, and cytokeratin 5/6 was positive. However, the anaplastic lymphoma kinase-V, thyroid transcription factor-1, synaptophysin, chromogranin A and napsin A were negative. Conclusions: Literature review showed that most of patients with peripheral EMC were asymptomatic. Computed tomography and magnetic resonance imaging scans are able to indicate the presence of peripheral EMC. Pathological analysis is an effective method to clarify the diagnosis. Surgery is a regular treatment method. To facilitate the preoperative diagnosis and avoid the misdiagnosis of such a rare disease, more cases will need to be reported.